Analysis of the Development of Islamic Accounting Research A Systematic Literature Review 2010–2025 (Al-Muwazanah: Indonesian Journal of Islamic Economics, 2025)
This study aims to analyze the development of Islamic accounting research during the period 2010–2025 using a Systematic Literature Review (SLR) approach. This approach was used to identify publication trends, key themes, research methods, and the future direction of Islamic accounting development. Data were obtained from 25 relevant national and international scientific journal articles through the Google Scholar, Scopus, and DOAJ databases. The analysis results show a significant increase in Islamic accounting research, especially after 2016, with a focus on zakat, Islamic governance, Islamic financial reporting, and the integration of Islamic principles (maqashid) of Islam. The majority of studies used qualitative methods, while new topics began to move towards the integration of digitalization and sustainability reporting. This study contributes to mapping the development and direction of Islamic accounting research to make it more relevant to the challenges of the modern economy